Intensity-Modulated Radiotherapy with a Simultaneous Integrated Boost Combined with Chemotherapy in Stages III-IV Hypopharynx-Larynx Cancer: Treatment Compliance and Clinical Outcomes. (30th January 2014) - Franchin, Giovanni; Vaccher, Emanuela; Talamini, Renato; Gobitti, Carlo; Minatel, Emilio; Furlan, Carlo; Grando, Giuseppe; Drigo, Annalisa; Trovo, Mauro Gaetano; Barzan, Luigi
Abstract : Objectives. Retrospective review of our experience using intensity-modulated radiotherapy with simultaneous integrated boost (SIB-IMRT) combined with chemotherapy as the primary treatment of locoregionally advanced larynx and hypopharynx cancers. Materials and Methods. Between September 2008 and June 2012, 60 patients (26 with larynx and 34 hypopharynx cancers) were treated. Our policy was to offer SIB-IMRT plus concurrent cisplatin to patients affected by larynx cancer stage T3N0-N1 and NCT with TPF (docetaxel/cisplatin/fluorouracil) followed by SIB-IMRT to patients with larynx cancer stage T2-4N2-3 or hypopharynx cancer T2-4N0-3. SIB-IMRT consisted in a total dose of 70.95 Gy (2.15 Gy/fraction, 5 fractions/week) to the gross primary and nodal disease and differentiated dosages for high risk and low risk nodal regions. Results. Complete remission was achieved in 53/60 (88%) of patients. At a median follow up of 31 months (range 9–67), the rate of overall survival and locoregional control with functional larynx at 3 years were 68% and 60%, respectively. T stage (T1–3 versus T4) resulted in being significant for predicting 3-year freedom from relapse (it was 69% and 35%, resp., for T1–T3 and T4 tumors;P = 0.04 ), while site of primary disease (larynx versus hypopharynx) was not significant (P = 0.35 ). Conclusion. Our results indicated that combining SIB-IMRT with induction chemotherapy or concurrent chemotherapy is an effective treatment strategy for organ preservation in advanced larynx/hypopharynx cancer.